Restorying With the Ancestors: Historically Rooted Speculative Composing Practices and Alternative Rhetorics of Queer Futurity. (October 2021) - Coleman, James Joshua
Within literacy, rhetoric, and composition (LRC) studies, composing practices have been studied as an embedded feature of life, one that manifests histories, imagination, and identities through acts of writing. Likewise, in queer LRC studies, the capacity to write with queer rhetorical agency or to recognize the impossibility of composing queer subjectivity has been tied to the living. Scholars have yet to consider with adequacy, however, the ways in which writing is equally bound up with the dead, with ghosts, histories, and ancestors that animate the imagination and attendant composing practices. Tracing the historically rooted speculative composing practices (HRSCPs) of an inquiry group of nine queer composers, this article spotlights queer ancestors as speculative resources for imagining and then composing alternative rhetorics of queer futurity. Specifically, this article details how three queer composers, Coyote (they/them), Helen (she/her), and Margarita (they/them), restory the imagination, happiness, and reality with the ancestors, doing so to challenge the trope of queer unhappy endings attached to realist genres. This article concludes by inviting LRC studies to explore how HRSCPs might be integrated into future research and pedagogy and thereby pursue healing for communities long marginalized within the field.